Mencapai Kesejahteraan Masyarakat Melalui Instrumen Zakat dan Wakaf: Studi Kasus Pengelolaan Wakaf Mesir Dan Indonesia - Muhammad Luqman El Hakim; Maryam Batubara; Elaeis Guineensis Jalil Hsb (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to provide an explanation of the comparison and similarity of zakat and waqf in Indonesia and Egypt. Both Indonesia and Egypt have government institutions that focus on managing zakat and waqf, both countries have special bodies responsible for zakat and waqf. From this research it is concluded that the management of zakat and waqf in Egypt and Indonesia has the aim of advancing welfare and development through waqf and zakat instruments in various fields, such as education, health, charity, poverty alleviation, economic development, micro-enterprises, and maintenance of places. Worship and things can continue to be used for the social, economic and religious benefit of society.